2013
DOI: 10.1177/1708538112472282
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of connective tissue growth factor, osteopontin and increased collagen content in human ascending thoracic aortic aneurysms

Abstract: Little is known about the molecular mechanisms of ascending thoracic aortic aneurysms (ATAAs). Abnormal extracellular matrix changes and variations of vascular smooth muscle cells (VSMCs) have been implicated in abdominal aortic aneurysm formation. Our objective was to investigate the alterations of collagen, stimulators of collagen synthesis and synthetic VSMCs in patients with ATAA. Surgical samples from ATAA were taken from 20 patients, and 18 control aortas were obtained during coronary artery bypass surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
2
25
1
3
Order By: Relevance
“…Induction of CTGF, a major collagen-deposition related factor, was reported in vascular smooth muscle cells after oxidative burst in thoracic aneurysms ex vivo [10]. A recent study reported higher level of CTGF, osteopontin-1, and collagen in human thoracic aneurysms when compared to CABG controls without significant difference in incidence of hypertension or diabetes [23]. Their results are in contrast to our data, probably due to the differences in the control group.…”
Section: Discussioncontrasting
confidence: 99%
“…Induction of CTGF, a major collagen-deposition related factor, was reported in vascular smooth muscle cells after oxidative burst in thoracic aneurysms ex vivo [10]. A recent study reported higher level of CTGF, osteopontin-1, and collagen in human thoracic aneurysms when compared to CABG controls without significant difference in incidence of hypertension or diabetes [23]. Their results are in contrast to our data, probably due to the differences in the control group.…”
Section: Discussioncontrasting
confidence: 99%
“…Collagen III, maintaining tensile strength and overall rigidity of the aorta, was also increased in the AAA tissues, which was in agreement with the results demonstrated by Pei et al . and Meng et al …”
Section: Discussionsupporting
confidence: 92%
“…31 Additionally, our results presented that ectopic expression of miR-195 up-regulated expressions of OPN and collagen III. Collagen III, maintaining tensile strength and overall rigidity of the aorta, was also increased in the AAA tissues, which was in agreement with the results demonstrated by Pei et al 32 and Meng et al 33 . On the contrary, collagen III was indicated to be down-regulated in ascending aortic aneurysm wall.…”
Section: Discussionsupporting
confidence: 92%
“…Some reports show a decreased expression of collagen in ascending aortic aneurysm wall, 21,22 whereas others show increased amounts. 6,23 It appears that either increases or decreases in collagen may weaken the aortic wall. In this study, the amount of collagen III increased in the wall of the ascending aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%